Introgression of Trifolium ambiguum Into Allotetraploid White Clover (Trifolium repens) Using the Ancestral Parent Trifolium occidentale as a Bridging Species - Ullah, Ihsan; Ansari, Helal A.; Verry, Isabelle M.; Hussain, Syed Wajid; Ellison, Nick W.; McManus, Michael T.; Williams, Warren M. (Frontiers in Plant Science, 2022)
White clover (Trifolium repens) is an allotetraploid pasture legume widely used in moist temperate climates, but its vulnerability to drought, grazing pressure and pests has restricted its wider use. A related species, Caucasian clover (Trifolium ambiguum), is a potential source of resistances to drought, cold, grazing pressure and pests that could potentially be transferred to white clover by interspecific hybridization. Although direct hybridization has been achieved with difficulty, the hybrids have not been easy to backcross for introgression breeding and no interspecific chromosome recombination has been demonstrated. The present work shows that interspecific recombination can be achieved by using Trifolium occidentale, one of the ancestral parents of T. repens, as a bridging species and that large white clover breeding populations carrying recombinant chromosomes can be generated. A 4x hybrid between T. ambiguum and T. occidentale was crossed with T. repens and then backcrossed for two generations. Five backcross hybrid plants with phenotypes appearing to combine traits from the parent species were selected for FISH-GISH analyses. Recombinant chromosome segments from T. ambiguum were found in all five plants, suggesting that recombination frequencies were significant and sufficient for introgression breeding. Despite early chromosome imbalances, the backcross populations were fertile and produced large numbers of seeds. These hybrids represent a major new resource for the breeding of novel resilient forms of white clover.